2013
DOI: 10.1039/c3cc45449e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of biaryl imino/keto carboxylic acids via aryl amide directed C–H activation reaction

Abstract: A novel Pd-catalysed C-H activation reaction for the synthesis of biaryl imino/keto carboxylic acids is developed. This reaction underwent aryl amide directed C-H activation ortho-acylation followed by ring closing and ring opening processes to give a range of biaryl imino/keto carboxylic acids. Our methodology features the utilization of a cheap and green oxidant (TBHP) as well as readily available aldehydes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…37 Oxidative C–H couplings with aromatic aldehydes were highly efficient, however, alkyl aldehydes were ineffective in the transformation.…”
Section: Aldehydesmentioning
confidence: 99%
“…37 Oxidative C–H couplings with aromatic aldehydes were highly efficient, however, alkyl aldehydes were ineffective in the transformation.…”
Section: Aldehydesmentioning
confidence: 99%
“…With N ‐substituted benzamides and aldehydes as the substrates, the desired hydroxyisoindolones were isolated in good yields (Scheme ). Interestingly, imino carboxylic acids can be prepared from the same substrates by simply adding the Lewis acid BF 3 ⋅ Et 2 O (Scheme ) 20b…”
Section: Discussionmentioning
confidence: 99%
“…From the Literature studies it is revealed that several oxidants such as air, [19a] Ag 2 CO 3 , [19b] PhI(OCOCF 3 ) 2 , [19c] (NH 4 ) 2 S 2 O 8 , [19d] K 2 S 2 O 8 , [19e,f] 3,3′,5,5′‐tetra‐ tert ‐butyldiphenoquinone (DPQ), [19g] peroxides [19h–k] i.e. Di‐ t ‐butyl peroxide (DTBP), dicumyl peroxide (DCP), (PhCOO) 2 , PhC(CH 3 ) 2 OOH, TBHP [ t ‐butyl hydroperoxide] and molecular oxygen (O 2 ) [19l] have been utilized for transition‐metal‐catalyzed oxidative coupling reaction with various acylating agents such as: aldehydes, α‐oxoacids, alcohols, arylmethyl amines, 1,2‐Diketone etc.…”
Section: Introductionmentioning
confidence: 99%